Constructing residents’ (un)deservingness and rights in the urban housing displacement processes - Juhila, Kirsi; Perälä, Riikka; Sippola, Lotta; Ranta, Johanna; Niemi, Veera (Taylor & Francis, 2025)
This study examines four housing displacement cases in Finnish cities, based on interviews with the residents and other actors involved in the displacement processes. It integrates theories from the housing displacement and deservingness literature. It asks what kinds of discourses on the residents’ deservingness and rights to housing and housing-related services are constructed in the interviews. The results demonstrate how binary discourses, namely ‘they don’t deserve better’ and ‘they deserve better’ are constructed in the interviews, and how the residents’ own talk reflects both discourses. The discourses resonate with the CARIN criteria established in previous studies on how people define deservingness, but their construction in the interviews was manifold, and were not confined to certain actors. The discourse that plays a dominant role is highly consequential for spatially vulnerable residents. Involuntary displacement evokes questions about who deserves to live in certain urban spaces and why, and what kind of housing the displaced residents are generally seen as entitled to.